2013
DOI: 10.1136/bcr-2012-008119
|View full text |Cite
|
Sign up to set email alerts
|

Brunneroma with duodenojejunal intussusception: a rare cause of gastric outlet obstruction

Abstract: Duodenal adenoma presenting with duodenojejunal intussusception is very rare. Only a few have ever been reported. Upon evaluation it may be difficult to rule out malignancy. The final diagnosis may be reached only at surgery and confirmed at histopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…[ 3 ] Furthermore, when the BGA lesions are larger in size, there are rare clinical manifestations incuding gastrointestinal obstruction pancreatitis and obstructive jaundice. [ 4 , 14 ] Our case presented with BGA-related blood loss, which led to hemodynamic instability. Although some studies have reported cases with gastrointestinal bleeding as the main clinical manifestation, [ 5 6 ] our case show larger lesion size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 3 ] Furthermore, when the BGA lesions are larger in size, there are rare clinical manifestations incuding gastrointestinal obstruction pancreatitis and obstructive jaundice. [ 4 , 14 ] Our case presented with BGA-related blood loss, which led to hemodynamic instability. Although some studies have reported cases with gastrointestinal bleeding as the main clinical manifestation, [ 5 6 ] our case show larger lesion size.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] However, others advocated endoscopic resection in order to prevent complications. [ 4 ] For symptomatic and larger BGA leading to gastrointestinal obstruction or bleeding, they usually needed endoscopic or surgical treatment. [ 4 , 16 17 ] When possible, endoscopic polypectomy or mucosal resection was advised, while for larger tumors or endoscopic interventions fail, the surgical resection should be carefully considered, bearing in mind the higher risk of complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If endoscopic removal fails or is unsuitable, surgical intervention may be required. Surgical options include polypectomy, pancreas-sparing duodenectomy or pancreaticoduodenectomy [27]. …”
Section: Discussionmentioning
confidence: 99%